The Effect of Taxpayer Knowledge, Modernization of The Tax Administration System, Tax Sanctions, Tax Awarness and Accountability of Public Service on The Compliance of Motor Vehicle Taxpayers - Nikmah, Alfiyatun; Mulyani, Ulva Rizky; Zuliyati (Universitas Pamulang, 2024)
This research aims to address the gap in understanding how factors influence motor vehicle taxpayer compliance. Specifically, the study examines the effect of taxpayer knowledge, modernization of the tax administration system, tax sanction, tax awarness and public service accountability on taxpayer compliance. The study focused on taxpayers registed at the Jepara Regency Samsat Office. A total of 400 respondents were selected using Accidental Sampling. Primary data was collected for this study. To analyze the data, Multiple Linier Regression Analysis was conducted using SPSS version 26. Which have a positive effect is taxpayer knowledge, modernization of the tax administration system and tax sanction. Meanwhile it have no effect is tax awarness and public service accountability.